2010
DOI: 10.1186/1471-2318-10-81
|View full text |Cite
|
Sign up to set email alerts
|

The differential impact of subjective and objective aspects of social engagement on cardiovascular risk factors

Abstract: BackgroundThis article provides new insights into the impact of social engagement on CVD risk factors in older adults. We hypothesized that objective (social participation, social ties and marital status) and subjective (emotional support) aspects of social engagement are independently associated with objective measures of cardiovascular risk.MethodsData from the English Longitudinal Study on Ageing (ELSA) were analyzed. The effects of social participation, social ties, marital status, and emotional support on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
3
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 63 publications
(69 reference statements)
3
40
3
3
Order By: Relevance
“…, Kamiya et al . ). Differences across population groups have not been well‐researched to date, but Wang et al .…”
Section: Resultsmentioning
confidence: 97%
“…, Kamiya et al . ). Differences across population groups have not been well‐researched to date, but Wang et al .…”
Section: Resultsmentioning
confidence: 97%
“…groups that are characterized by non‐hierarchical, egalitarian relationships among group members; volunteer, sport and hobby groups in their study) was inversely associated with hypertension among older people in Japan . Kamiya et al showed that participating in a greater number of organizations was associated with a lower odds of hypertension among the older population living in the UK …”
Section: Introductionmentioning
confidence: 99%
“…First, we used longitudinal dataset and investigated the association to deal with the issue of reverse causality. Previous studies used a cross‐sectional design to investigate the association . Second, few studies have been carried out in China, which exemplifies rapid economic development and population aging in the past several decades better than any other countries and thus, the increasing trend of hypertension .…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization’s International Classification of Functioning, Disability and Health (ICF) has helped to highlight social participation as both a determinant of health 24 and as a treatment outcome valued by patients, providers and policy makers. 5 Participation in social roles and discretionary activities is included in the ICF’s core sets for chronic heart failure (CHF), chronic obstructive pulmonary disease (COPD), back pain and depression.…”
Section: Introductionmentioning
confidence: 99%